Recent trends in allocation of risk post-macondo: the growing tension between oil and gas standard forms of contract, and contractual practice - Wan Zahari, Wan Mohd Zulhafiz (Thomson Reuters, 2017)
The oil and gas industry is exposed to substantial risks and huge liabilities, due to its nature dealing with wide ranges of activities that engage volatile hydrocarbons. The risks mostly involve people, property, and the environment. A contractual provision such as an indemnity and mutual hold harmless clause is used as a tool in allocating the risks. However, some of the contractual indemnification provisions that are employed in the industry were criticised for being biased particularly subsequent to the Macondo disaster in the Gulf of Mexico in 2010. It is claimed that operators have attempted to depart from the established standard model forms of contracts and to shift greater risk to the contractor in the event of a catastrophe. This problem could lead to financial detriment and unfairness to the contractor. This paper seeks to analyse such phenomenon and the Macondo case. It will be carried out in a descriptive, analytic, and prescriptive manner.